E1.4 First experiences and diagnostic utility of micro-ct for fetal autopsy. (4th October 2017) - Hutchinson, JC; Kang, X; Shelmerdine, SC; Segers, VS; Lombardi, CM; Cannie, MM; Sebire, NJ; Jani, JC; Arthurs, OJ
Abstract : Background: Perinatal autopsy remains poorly accepted by parents, despite yielding information that affects the management of future pregnancies in around 30% of cases. Microcomputed tomography (micro-CT) has shown promising results in the examination of ex-vivo fetal organs, and may provide diagnostic imaging in cases where traditional autopsy is challenging, and existing post mortem imaging techniques (CT and MRI) provide insufficient diagnostic resolution. Our objective was to examine whole fetuses non-invasively using micro-CT, and compare the findings with standard autopsy as the gold standard. Methods: In this ethically approved double blinded study, terminated fetuses or miscarriages underwent iodinated micro-CT examination followed by conventional autopsy. Images were acquired using a Nikon XTH225ST microfocus-CT scanner with individual specimen image optimisation. Forty indices normally assessed at perinatal autopsy were evaluated for each imaging dataset by two independent reporters and a consensus report produced. Autopsies were performed blinded to the imaging findings by one of two perinatal pathologists. Results: We examined 8 fetuses, with a gestational age range of 11–16 gestational weeks. 36/320 indices were non-diagnostic (11%), but there was agreement for 271/284 diagnostic indices (overall concordance of 95.4% (95% CI 92.3, 97.3%). In seven out of eight fetuses (87.5%), the same final diagnosis was made following micro-CT examination and autopsy examination; in one case, micro-CT was non-diagnostic. Ten false negatives indices included a VSD, laryngeal anomaly, ambiguous genitalia and incomplete bowel rotation, none of which changed the overall diagnosis. Three apparent false positives on micro CT were a cloacal anomaly, incidental cystic neck lesion and thymic atrophy, which were not detected at autopsy. Conclusion: Micro-CT of early gestation whole fetuses can provide highly accurate datasets with three-dimensional renderings of complex disease processes. This approach confirms the potential of this technology for non-invasive examination of small fetuses.